A mathematical model for the spread of west nile virus in migratory and resident birds - Louis D. Bergsman; James M. Hyman; Carrie A. Manore (Mathematical Biosciences and Engineering)
We develop a mathematical model for transmission of West Nile virus (WNV) that incorporates resident and migratory host avian populations and a mosquito vector population.We provide a detailed analysis of the model's basic reproductive number and demonstrate how theexposed infected, but not infectious, state for the bird population can be approximated by a reduced model.We use the model to investigate the interplay of WNV in both resident and migratory bird hosts. The resident host parameters correspond to the American Crow (Corvus brachyrhynchos), a competent host with a high death rate due to disease, and migratory host parameters to the American Robin (Turdus migratorius), a competent host with low WNV death rates. We find that yearly seasonal outbreaks depend primarily on the number of susceptible migrant birds entering the local population each season.We observe that the early growth rates of seasonal outbreaks is more influenced by thethe migratory population than the resident bird population.This implies that although the death of highly competent resident birds, such as American Crows,are good indicators for the presence of the virus, these species have less impact on the basic reproductive number than the competent migratory birds with low death rates, such as the American Robins.The disease forecasts are most sensitive to the assumptions about the feeding preferences of North American mosquito vectors and the effect of the virus on the hosts. Increased research on the these factors would allow for better estimates of these important model parameters, which would improve the quality of future WNV forecasts.